Case Report: Trigeminocardiac Reflex in Endovascular Recanalization of Intracranial Internal Carotid Artery Occlusion - Ren, Hecheng; Wang, Yubo; Luo, Bin; Ma, Lin; Ma, Yuxiang; Yin, Long; Huang, Ying (Frontiers in Neurology, 2022)
Background The trigeminocardiac reflex (TCR) is a unique brainstem reflex that manifests as sudden negative hemodynamic changes. Although rare, TCR may develop during interventional neuroradiology procedures. Intracranial internal carotid artery occlusion (ICAO) is a cause or risk factor of ischemic stroke. Endovascular recanalization is an effective treatment for intracranial ICAO. The occurrence of TCR during the endovascular treatment of intracranial ICAO has not been reported previously. Methods We identified and reviewed four intracranial ICAO cases who suffered a sudden negative hemodynamic change during endovascular therapy at our hospital between March 2019 and December 2020. Results There were five sudden heart rate and/or blood pressure drops in the four cases; all occurred just after contrast agents were injected. Some angioarchitectural characteristics were common among the four cases. First, the intracranial internal carotid artery distal to the ophthalmic artery was occluded, leaving the ophthalmic artery as the only outflow tract. Second, there were obstructive factors proximal to the end of the guiding catheter, including a vasospasm or dilated balloon. This type of angioarchitecture with a limited outflow tract creates a “blind alley.” The five negative hemodynamic events all recovered: two spontaneously and three after drug administration. Postoperatively, two of the four patients developed ocular symptoms. Conclusions Intracranial ICAOs may produce a distinctive angioarchitecture, such as a blind alley, that predisposes patients to TCR. Surgeons should pay special attention to the possibility of TCR during the endovascular recanalization of intracranial ICAO. Low-pressure contrast injections should be attempted, and anticholinergics should be ready for use.